The legal treatment of distance learning in the light of e-learning data - Madb Mohammed Al-Obeidi., Dr. Sami (The college of law and political science journal, 2023)
The distance learning system is one of the fruits of globalizationWhich in turn was one of the fruits of what the world has reached in terms ofmodern and advanced technology in the science of communication so much thatthe world has become a small village like any hose anywhere in world .It is well known that this revolution of communication led to great outcomes,in clouding the emergence of a distance learning system, not only that, but thissystem of education was adopted at the beginning of research centers and privateeducational institutions.